"I Haven't Given Up and I'm Not Gonna": A Phenomenographic Exploration of Resilience Among Individuals Experiencing Homelessness. (November 2019) - Shankar, Sneha; Gogosis, Evie; Palepu, Anita; Gadermann, Anne M.; Hwang, Stephen W.
Resilience is a factor related to positive health outcomes. Exploring this concept among adults experiencing homelessness can inform interventions while subsequently considering individuals' strengths. A phenomenographic approach was applied to examine this concept among a sample of 22 individuals involved in qualitative interviews. The phenomenographic inquiry identified eight conceptions and found resilience is captured in both positive and negative ways. Conceptions are summarized by two categories, situated in an outcome space which describes the overall resilience experience and the different ways these conceptions are understood and experienced. Categories summarize conceptions as Staying Strong and Sustaining Positive Beliefs, which highlight the construct as being captured by a persistent positive aspect; however, the findings also uniquely describe the influence of negative conceptions toward the overall phenomenon. The findings suggest resilience is recognizable during adversity, and it is a phenomenon that has the potential to be strengthened.